Assessing knowledge management readiness in organizations - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza, Abdul Karim (2010)
The importance of measuring organizational readiness to implement knowledge management (KM) process has been well documented in the literature from both practitioners’ and academics’ perspectives. However, very limited information is available in the literature in this regard. Hence, the present authors propose a research model by integrating knowledge creation theory (SECI process), KM enablers, and individual acceptance models. In addition, an instrument that can be used to measure the KM readiness of an organization also presented. The reliability of the proposed instrument was tested among 222 executives in the Sri Lanka Telecommunication Industry.